Preparation method of novel polycarbosilane alumina ceramic composite membrane
By adjusting the organic solution system, the mixture of polycarbosilane and polysulfone-polyethylene glycol block copolymer and alumina ceramic particles is achieved to prepare a ceramic composite film in one step, which solves the long preparation period and uneven pore size of the ceramic film Problem, improving the porosity and selectivity of the membrane.
Patent Information
- Application Number
- CN202310686090.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-12
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-06-12
AI Technical Summary
The existing ultrafiltration ceramic membrane with high separation accuracy has a long preparation cycle, complex process, and high cost. The small particle size ceramic filler leads to large pores and uneven distribution of the membrane, making it difficult to prepare complete ceramic sheets.
By screening and adjusting the mixed organic solution system, the polycarbosilane is dissolved and added to the mixed slurry of polysulfone-polyethylene glycol block copolymer and alumina ceramic particles to achieve one-step phase conversion and curing, and ultra-thin and pore size are prepared Small and even distribution of ceramic composite film.
The pore size and distribution of the ceramic membrane are significantly sharpened, which improves the porosity and oil-water selection permeability of the ceramic membrane, reduces the preparation steps and costs, and achieves low-cost ceramic membrane production.
Smart Images

Figure CN119113818A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic film processing, and in particular relates to a novel ceramic composite film prepared by polycarbosilane shrinkage pores and a preparation method thereof. Background Art
[0002] As an important separation membrane material, ceramic membranes are widely used in various water treatment processes due to their good anti-pollution performance, material stability, high mechanical strength and other advantages. However, the current ultrafiltration ceramic membranes with high separation accuracy usually need to undergo multiple coating-sintering processes, which results in long preparation cycles, complex processes, and high costs for ceramic membranes, limiting the low-cost development process of ceramic membrane applications. Using small-particle ceramic fillers mixed into the membrane slurry for pore shrinkage is currently a feasible solution. However, serious agglomeration between particles of different sizes easily results in large membrane pores, uneven distribution, and low particle loading.
[0003] Polycarbosilane (PCS) is an organosilicon polymer connected by Si-C bonds, with a chemical formula of [Si-C]n, which can be dissolved in some organic solvents. As an organosilicon polymer containing a large amount of silicon and carbon elements, it can be vitrified into ceramic particles such as SiC or SiOC under certain high-temperature pyrolysis conditions. Therefore, it can be used as a ceramic precursor to prepare ceramics. However, the currently reported impregnation cracking scheme, on the one hand, increases the number of sintering times of the membrane, and on the other hand, due to the large volume shrinkage of the organic phase of polycarbosilane during the transformation to inorganic ceramics, and at the same time, a large amount of small molecular gas is released, causing the porous ceramic membrane to crack easily, making it difficult to prepare a complete ceramic sheet. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a method for preparing a novel polycarbosilane-alumina ceramic composite membrane. The present invention selects and adjusts the mixed organic solution system so that the polycarbosilane is successfully added to the mixed slurry of polysulfone-polyethylene glycol block copolymer and alumina ceramic particles after being dissolved, and at the same time realizes one-step phase conversion curing to form a membrane, so that the polycarbosilane can be in-situ sintered with the solid particles in the green membrane into an ultra-thin separation membrane material with a small and uniform pore size distribution.
[0005] The novel ceramic composite membrane prepared from polycarbosilane alumina described in the present invention is composed of the following raw materials in percentage by mass:
[0006] Ceramic powder 30%-45%,
[0007] Polycarbosilane (PCS) 1%-10%,
[0008] Polysulfone-polyethylene glycol block copolymer 6%-10%,
[0009] Surfactant 1%-2%,
[0010] The rest is a mixed organic solvent of tetrahydrofuran and N,N-dimethylpyrrolidone, and the surfactant is composed of poloxamer and Arlacel-P135.
[0011] Specifically, the ceramic powder of the present invention is at least one of metal oxides such as aluminum oxide, silicon oxide, and zirconium oxide.
[0012] Specifically, the molecular weight of the polycarbosilane of the present invention is 1000-2000, and the melting point is between 200-220°C.
[0013] Specifically, the proportion of polyethylene glycol in the polysulfone-polyethylene glycol block copolymer of the present invention is 17 wt %. The preparation method of the polysulfone-polyethylene glycol block copolymer can refer to the article "Preparation of amphiphilic polysulfone block copolymer and its application in separation membrane field" published by our research group.
[0014] Specifically, the mass ratio of poloxamer to Arlacel-P135 in the surfactant of the present invention is 1-2:1.
[0015] Specifically, the organic solvent of the present invention is a mixed system of NN-methylpyrrolidone and tetrahydrofuran, wherein the preferred ratio of the organic solvent is 2-3:1.
[0016] The present invention also provides a method for preparing the novel polycarbosilane alumina ceramic composite membrane, comprising the following steps:
[0017] S1. Prepare casting solution
[0018] Weigh the raw materials in proportion, first dissolve the polysulfone-polyethylene glycol block copolymer and the surfactant in a mixed solution of NN-dimethylpyrrolidone and tetrahydrofuran, then add solid polycarbosilane and stir to dissolve, finally add solid ceramic powder and perform ball milling, mix evenly to obtain a slurry casting solution with fluidity;
[0019] S2, degassing
[0020] The casting solution is subjected to ultrasonic degassing in ice water, and then subjected to low-temperature vacuum degassing;
[0021] S3, solidification
[0022] The degassing casting liquid is poured onto a clean glass plate and scraped into a liquid film, and then immersed in a polar solvent, so that the liquid film on the glass plate solidifies and falls off the glass plate to form a preliminary film, wherein the polar solvent is anhydrous ethanol, the curing time is 1-5 hours, and the curing temperature is preferably room temperature;
[0023] S4, high temperature sintering to make ceramic membrane
[0024] The green film is placed in a tube furnace and sintered by programmed temperature to form a ceramic film; the programmed temperature includes three stages, as follows:
[0025] The first stage is to heat from room temperature to 220℃ and keep it for 0.5h;
[0026] The second stage is to increase the temperature from 220℃ to 700℃ and keep it at this temperature for 2h;
[0027] The third stage is to increase the temperature from 700℃ to 1350℃ and keep it at this temperature for 2h.
[0028] Preferably, during ultrasonic degassing in step S2 of the present invention, the ultrasonic power is 150-200w, the ultrasonic frequency is 30-50kHz, the ultrasonic time is 10-30min, and it is preferably carried out in ice water.
[0029] Preferably, the vacuum degree during vacuum degassing in step S2 of the present invention is -101.325 kPa, and it is preferably carried out at a low temperature in ice water.
[0030] Preferably, the rate of programmed temperature increase in the present invention is 3-4°C / min.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1) The ceramic composite membrane prepared by polycarbosilane shrinkage in the present invention has a thickness of 200-250 μm, and the pore size distribution is between 59-86 nm after one-step preparation, and 1%-10% polycarbosilane is uniformly added to the material, which significantly sharpens the pore size and distribution of the ceramic membrane (the average pore size is 76 nm), while the porosity of the ceramic membrane is maintained at 59%-65%.
[0033] 2) The present invention adds a polysulfone-polyethylene glycol block copolymer and a second solvent to the raw material system, so that the polycarbosilane can be dissolved and evenly mixed with the ceramic particles to form a casting liquid with a low viscosity and a high ceramic loading. The casting liquid can be made into an ultra-thin liquid film on a glass plate, and the liquid film can then be solidified in a polar solvent into a smooth and uniform primary film, in which the ceramic precursor and the binder polymer chain are evenly mixed with each other.
[0034] 3) The ceramic composite membrane prepared by polycarbosilane shrinkage pores described in the present invention has a small and narrow pore size distribution and good oil-water selective permeability. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a SEM image of a ceramic composite membrane prepared from polycarbosilane alumina in Example 10 of the present invention;
[0036] Figure 2 This is a SEM image of the alumina ceramic membrane prepared in Comparative Example 1 of the present invention;
[0037] Figure 3 This is a SEM image of the alumina ceramic composite membrane prepared in Comparative Example 2 of the present invention; DETAILED DESCRIPTION
[0038] The present invention is further described below in conjunction with specific examples. The polysulfone-polyethylene glycol block copolymer used in the following examples has a polyethylene glycol content of 17 wt%, a melting point of polycarbosilane of 220°C, a molecular weight of 1200, and an organic solvent of N-methylpyrrolidone and tetrahydrofuran in a ratio of 1:2.5. The pore size detection method is as follows:
[0039] The pore size and distribution of the membrane samples were characterized using the Porolux 1000 capillary flow pore size analyzer from the Belgian Porometer Company. The method used was the wet-dry curve method to test the pore size. The specific operation was to first soak the sample to be tested in the Porefil wetting solution (surface tension 16 dyn / cm) 10 minutes before the test until the membrane pores were completely wetted. The wetted membrane was then taken out and placed in a membrane pool padded with a metal gasket and a sealed membrane pool. The wet-dry curve of the membrane sample was tested by the test method of first measuring the wet curve and then testing the dry curve, and the pore size test data was derived from the test instrument.
[0040] Examples 1-4
[0041] A method for preparing a novel polycarbosilane alumina ceramic composite membrane is as follows:
[0042] S1. Prepare casting solution
[0043] 45wt% of alumina powder with a particle size of 200nm, 3wt% of polycarbosilane, and 1.5wt% of surfactant were weighed and dissolved in a mixed organic solvent, and then 6wt% of polysulfone-polyethylene glycol block copolymer was added. The surfactant was composed of poloxamer and Arlacel-P135 in a mass ratio of 1:1 (the mass percentage of each substance is the percentage of the total mass of the feed solution);
[0044] S2, degassing
[0045] The casting liquid is placed in ice water for ultrasonic degassing treatment, wherein the ultrasonic power is 180w, the ultrasonic frequency is 40kHz, and the ultrasonic time is 30min; then vacuum degassing is performed in an ice water bath at a vacuum degree of -101.325kPa to eliminate smaller bubbles in the casting liquid.
[0046] S3, solidification
[0047] The degassing casting liquid is poured onto a clean glass plate and scraped into a liquid film with a thickness of 250 μm, and then immersed in water at room temperature for curing for 4 hours, so that the liquid film on the glass plate is solidified and falls off the glass plate to form a preliminary film;
[0048] S4, high temperature sintering to make ceramic membrane
[0049] The green film is placed in a sintering furnace and subjected to programmed temperature sintering to form a ceramic film; the programmed temperature rise includes three stages, and the heating rate of each stage is 3-4°C, as follows:
[0050] The first stage is to heat from room temperature to 220℃ and keep it for 0.5h;
[0051] The second stage is to increase the temperature from 220℃ to 700℃ and keep it at this temperature for 2h;
[0052] The third stage is to increase the temperature from 700℃ to 1350℃ and keep it at this temperature for 2h.
[0053] One of the mixed solvents in Examples 1-4 is N-methylpyrrolidone, and the other is any one of common organic solvents such as xylene, n-hexane, 1,4-epoxyhexadecane, tetrahydrofuran, etc. The two organic solvents are mixed in a mass ratio of 1:1. The results of Examples 1-4 are shown in Table 1
[0054]
[0055] The large flake particles on the membrane surface are caused by the PCS not being mixed evenly with the binder in the mixed solvent. The results in Table 1 in the case show that the polymer binder polysulfone-polyethylene glycol block copolymer and PCS can be well dissolved and mixed with each other when N-methylpyrrolidone and tetrahydrofuran are used as mixed solvents.
[0056] Embodiment 5-9
[0057] A method for preparing a novel polycarbosilane alumina ceramic composite membrane is as follows:
[0058] S1. Prepare casting solution
[0059] 45wt% of alumina powder with a particle size of 200nm, 3wt% of polycarbosilane, and 1.5wt% of surfactant were weighed and dissolved in a mixed solvent of N-methylpyrrolidone and tetrahydrofuran in different proportions, and then 6wt% of polysulfone-polyethylene glycol block copolymer was added. The surfactant was composed of poloxamer and Arlacel-P135 in a mass ratio of 1:1 (the mass percentage of each substance is the percentage of the total mass of the feed liquid);
[0060] S2, degassing
[0061] The casting liquid is placed in ice water for ultrasonic degassing treatment, wherein the ultrasonic power is 180w, the ultrasonic frequency is 40kHz, and the ultrasonic time is 30min; then vacuum degassing is performed in an ice water bath at a vacuum degree of -101.325kPa to eliminate smaller bubbles in the casting liquid.
[0062] S3, solidification
[0063] The degassing casting liquid is poured onto a clean glass plate and scraped into a liquid film with a thickness of 250 μm, and then immersed in water at room temperature for curing for 4 hours, so that the liquid film on the glass plate is solidified and falls off the glass plate to form a preliminary film;
[0064] S4, high temperature sintering to make ceramic membrane
[0065] The green film is placed in a sintering furnace and subjected to programmed temperature sintering to form a ceramic film; the programmed temperature rise includes three stages, and the heating rate of each stage is 3-4°C, as follows:
[0066] The first stage is to heat from room temperature to 220℃ and keep it for 0.5h;
[0067] The second stage is to increase the temperature from 220℃ to 700℃ and keep it at this temperature for 2h;
[0068] The third stage is to increase the temperature from 700℃ to 1350℃ and keep it at this temperature for 2h.
[0069] The ratio of organic solvent N-methylpyrrolidone to tetrahydrofuran in Examples 5-9 is 1:1, 1:2, 1:2.5, 1:3, 1:4, 0:1. The results of the examples are shown in Table 2:
[0070]
[0071] By observing the particle size and surface morphology of the ceramic composite membrane prepared by polycarbosilane shrinkage, when the ratio of the mixed solvent composed of N-methylpyrrolidone and tetrahydrofuran is 1:2.5, PCS is completely dissolved and evenly mixed in the slurry for preparing the primary membrane, and small ceramic particles are formed in situ. The average pore size of the prepared membrane is 153nm, and the pore size distribution range is 98-225nm.
[0072] Example 10 / 11
[0073] A method for preparing a novel polycarbosilane alumina ceramic composite membrane is as follows:
[0074] S1. Prepare casting solution
[0075] 45wt% of alumina powder with a particle size of 200nm, 6 / 9wt% of polycarbosilane, and 1.5wt% of surfactant were weighed and dissolved in a mixed organic solvent of N-methylpyrrolidone and tetrahydrofuran with a mass fraction of 1:2.5, and then 6wt% of polysulfone-polyethylene glycol block copolymer was added. The surfactant was composed of poloxamer and Arlacel-P135 with a mass ratio of 1:1 (the mass percentage of each substance is the percentage of the total mass of the feed liquid);
[0076] S2, degassing
[0077] The casting liquid is placed in ice water for ultrasonic degassing treatment, wherein the ultrasonic power is 180w, the ultrasonic frequency is 40kHz, and the ultrasonic time is 30min; then vacuum degassing is performed in an ice water bath at a vacuum degree of -101.325kPa to eliminate smaller bubbles in the casting liquid.
[0078] S3, solidification
[0079] The degassing casting liquid is poured onto a clean glass plate and scraped into a liquid film with a thickness of 250 μm, and then immersed in water at room temperature for curing for 4 hours, so that the liquid film on the glass plate is solidified and falls off the glass plate to form a preliminary film;
[0080] S4, high temperature sintering to make ceramic membrane
[0081] The green film is placed in a sintering furnace and subjected to programmed temperature sintering to form a ceramic film; the programmed temperature rise includes three stages, and the heating rate of each stage is 3-4°C, as follows:
[0082] The first stage is to heat from room temperature to 220℃ and keep it for 0.5h;
[0083] The second stage is to increase the temperature from 220℃ to 700℃ and keep it at this temperature for 2h;
[0084] The third stage is to increase the temperature from 700℃ to 1350℃ and keep it at this temperature for 2h.
[0085] The average pore size of the prepared membrane composite ceramic membrane is 76nm, and the pore size distribution is 59-86nm
[0086] Comparative Example 1
[0087] A method for preparing a novel polycarbosilane alumina ceramic composite membrane is as follows:
[0088] S1. Prepare casting solution
[0089] 45wt% of alumina powder with a particle size of 200nm and 1.5wt% of surfactant are weighed and dissolved in a mixed organic solvent of N-methylpyrrolidone and tetrahydrofuran with a mass fraction of 1:2.5, and then 6wt% of polysulfone-polyethylene glycol block copolymer is added. The surfactant is composed of poloxamer and Arlacel-P135 with a mass ratio of 1:1 (the mass percentage of the prepared material is the percentage of the total mass of the feed liquid);
[0090] S2, degassing
[0091] The casting liquid is placed in ice water for ultrasonic degassing treatment, wherein the ultrasonic power is 180w, the ultrasonic frequency is 40kHz, and the ultrasonic time is 30min; then vacuum degassing is performed in an ice water bath at a vacuum degree of -101.325kPa to eliminate smaller bubbles in the casting liquid.
[0092] S3, solidification
[0093] The degassing casting liquid is poured onto a clean glass plate and scraped into a liquid film with a thickness of 250 μm, and then immersed in water at room temperature for curing for 4 hours, so that the liquid film on the glass plate is solidified and falls off the glass plate to form a preliminary film;
[0094] S4, high temperature sintering to make ceramic membrane
[0095] The green film is placed in a sintering furnace and subjected to programmed temperature sintering to form a ceramic film; the programmed temperature rise includes three stages, and the heating rate of each stage is 3-4°C, as follows:
[0096] The first stage is to heat from room temperature to 220℃ and keep it for 0.5h;
[0097] The second stage is to increase the temperature from 220℃ to 700℃ and keep it at this temperature for 2h;
[0098] The third stage is to increase the temperature from 700℃ to 1350℃ and keep it at this temperature for 2h.
[0099] The average pore size of the prepared membrane composite ceramic membrane is 291nm, and the pore size distribution is 194-403nm
[0100] Comparative Example 2
[0101] A method for preparing a novel polycarbosilane alumina ceramic composite membrane is as follows:
[0102] S1. Prepare casting solution
[0103] 45wt% of alumina powder with a particle size of 200nm, 8wt% of alumina ceramic particles with a particle size of 30nm, and 1.5wt% of a surfactant were weighed and dissolved in a mixed organic solvent of N-methylpyrrolidone and tetrahydrofuran with a mass fraction of 1:2.5, and then 8wt% of a polysulfone-polyethylene glycol block copolymer was added. The surfactant was composed of poloxamer and Arlacel-P135 with a mass ratio of 1:1 (the mass percentage of each substance is the percentage of the total mass of the feed liquid);
[0104] S2, degassing
[0105] The casting liquid is placed in ice water for ultrasonic degassing treatment, wherein the ultrasonic power is 180w, the ultrasonic frequency is 40kHz, and the ultrasonic time is 30min; then vacuum degassing is performed in an ice water bath at a vacuum degree of -101.325kPa to eliminate smaller bubbles in the casting liquid.
[0106] S3, solidification
[0107] The degassing casting liquid is poured onto a clean glass plate and scraped into a liquid film with a thickness of 250 μm, and then immersed in water at room temperature for curing for 4 hours, so that the liquid film on the glass plate is solidified and falls off the glass plate to form a preliminary film;
[0108] S4, high temperature sintering to make ceramic membrane
[0109] The green film is placed in a sintering furnace and subjected to programmed temperature sintering to form a ceramic film; the programmed temperature rise includes three stages, and the heating rate of each stage is 3-4°C, as follows:
[0110] The first stage is to heat from room temperature to 220℃ and keep it for 0.5h;
[0111] The second stage is to increase the temperature from 220℃ to 700℃ and keep it at this temperature for 2h;
[0112] The third stage is to increase the temperature from 700℃ to 1350℃ and keep it at this temperature for 2h.
[0113] The average pore size of the prepared membrane composite ceramic membrane is 250nm, and the pore size distribution is 177-398nm.
[0114] Comparative Example 3
[0115] A method for preparing a novel polycarbosilane alumina ceramic composite membrane is as follows:
[0116] S1. Prepare casting solution
[0117] 45wt% of alumina powder with a particle size of 200nm, 8wt% of polysulfone-binder, and 1.5wt% of surfactant were weighed and dissolved in a mixed organic solvent of N-methylpyrrolidone and tetrahydrofuran with a mass fraction of 1:2.5, and then 8wt% of polysulfone-polyethylene glycol block copolymer was added. The surfactant was composed of poloxamer and Arlacel-P135 with a mass ratio of 1:1 (the mass percentage of each substance is the percentage of the total mass of the feed liquid);
[0118] S2, degassing
[0119] The casting liquid is placed in ice water for ultrasonic degassing treatment, wherein the ultrasonic power is 180w, the ultrasonic frequency is 40kHz, and the ultrasonic time is 30min; then vacuum degassing is performed in an ice water bath at a vacuum degree of -101.325kPa to eliminate smaller bubbles in the casting liquid.
[0120] S3, solidification
[0121] The degassing casting liquid is poured onto a clean glass plate and scraped into a liquid film with a thickness of 250 μm, and then immersed in water at room temperature for curing for 4 hours, so that the liquid film on the glass plate is solidified and falls off the glass plate to form a preliminary film;
[0122] S4, high temperature sintering to make ceramic membrane
[0123] The green film is placed in a sintering furnace and subjected to programmed temperature sintering to form a ceramic film; the programmed temperature rise includes three stages, and the heating rate of each stage is 3-4°C, as follows:
[0124] The first stage is to heat from room temperature to 220℃ and keep it for 0.5h;
[0125] The second stage is to increase the temperature from 220℃ to 700℃ and keep it at this temperature for 2h;
[0126] The third stage is to increase the temperature from 700℃ to 1350℃ and keep it at this temperature for 2h.
[0127] The average pore size of the prepared membrane composite ceramic membrane is 218 nm, and the pore size distribution is 157-255 nm.
[0128] The results of Examples 7, 10, 11 and Comparison 1-3 are summarized as shown in Table 3.
[0129]
[0130] The ceramic membranes prepared in the examples and comparative examples were subjected to separation tests, and an oil-water emulsion with a wide particle size distribution was selected as the feed liquid. The specific method is as follows:
[0131] A common high-viscosity lubricating oil was used at a mass ratio of 1:1000 to prepare an oil-water emulsion stabilized by a surfactant with a concentration of 1000ppm. After high-speed stirring, the particle size distribution range was 0.05-0.5μm. The specific operation was to soak the sintered spare dry membrane in deionized water for about 10 minutes before testing, and then load it into the vertical cross-flow membrane pool. The actual effective test membrane area was 2.25cm 2 For each membrane performance test, the average value and standard deviation of at least 3 parallel samples were taken.
[0132] The separation effect in the embodiment is shown in Table 4
[0133]
[0134] It should be noted that the above are only some specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and other variations are possible. All variations directly or indirectly derived from the disclosure of the present invention by those skilled in the art should be considered as the protection scope of the present invention.
Claims
1. A method for preparing a novel polycarbosilane alumina ceramic composite membrane, characterized in that: It is composed of the following raw materials in percentage by mass: Alumina powder 30%-45%, Polycarbosilane (PCS) 1%-10%, Polysulfone-polyethylene glycol block copolymer 6%-10%, Surfactant 1%-2%, The rest is a mixed organic solvent of tetrahydrofuran and N,N-dimethylpyrrolidone, and the surfactant is composed of poloxamer and Arlacel-P135.
2. The novel ceramic composite membrane prepared from polycarbosilane alumina according to claim 1, characterized in that: The ceramic powder is at least one of metal oxides such as aluminum oxide, silicon oxide, and zirconium oxide.
3. The novel ceramic composite membrane prepared from polycarbosilane alumina according to claim 1, characterized in that: The polycarbosilane accounts for 1-12 wt %, has a molecular weight of 1000-2000, and a melting point of 200±20° C.
4. The novel ceramic composite membrane prepared from polycarbosilane alumina according to claim 1, characterized in that: The mass ratio of poloxamer to Arlacel-P135 in the surfactant is 1-2:
1.
5. The novel ceramic composite membrane prepared from polycarbosilane alumina according to claim 1, characterized in that: The organic solvent is a mixed dual solvent system, wherein the ratio of tetrahydrofuran to N,N-dimethylpyrrolidone is 2-3:
1.
6. The novel ceramic composite membrane prepared from polycarbosilane alumina according to claim 1, characterized in that: The hydrophilic end polyethylene glycol in the polyethersulfone polyethylene glycol block accounts for 17% of the block molecular chain.
7. The method for preparing a novel ceramic composite membrane prepared from polycarbosilane alumina according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Prepare casting solution Weigh the raw materials in proportion, first dissolve the polysulfone-polyethylene glycol block copolymer and the surfactant in a mixed solution of NN-dimethylpyrrolidone and tetrahydrofuran, then add the solid polycarbosilane and stir to dissolve, finally add the ceramic powder and perform ball milling, mix evenly to obtain a slurry casting solution with fluidity; S2, degassing The casting solution is subjected to ultrasonic degassing in ice water, and then subjected to low-temperature vacuum degassing; S3, solidification The degassing casting liquid is poured onto a clean glass plate, scraped to form a liquid film, and then immersed in a polar solvent until it solidifies and falls off the glass plate to form a preliminary film, wherein the polar solvent is anhydrous ethanol; S4, high temperature sintering to make ceramic membrane The green film is naturally dried and then placed in a tube furnace for programmed temperature sintering to form a ceramic film; the programmed temperature sintering includes three stages, as follows: The first stage is to heat from room temperature to 220℃ and keep it for 0.5h; The second stage is to increase the temperature from 220℃ to 700℃ and keep it at this temperature for 2h; The third stage is to increase the temperature from 700℃ to 1350℃ and keep it at this temperature for 2h.
8. The preparation method according to claim 7, characterized in that: During the ultrasonic degassing in step S2, the ultrasonic power is 150-200w, the ultrasonic frequency is 30-50kHz, the ultrasonic time is 10-50min, and it is carried out in ice water.
9. The preparation method according to claim 7, characterized in that: The rate of the programmed temperature increase is 3-4°C / min.
10. The preparation method according to claim 7, characterized in that: A ceramic precursor (polycarbosilane) was added to the mixed organic solvent as a pore shrinkage filler, and the preparation and pore shrinkage of a new ultrafiltration ceramic composite membrane were completed in one step through a phase inversion method.
Citation Information
Patent Citations
Preparation method of separation membrane based on high-solid-content silicon carbide slurry
CN111470869A
Halloysite nanotube reinforced ultrathin ceramic membrane and preparation method thereof
CN113842787A
Composition comprising block copolymer, and method for producing siliceous film using the same
US20220204704A1
